FREQUENCY OF ACQUIRED DYSFIBRINOGENEMIA AMONG CHRONIC LIVER DISEASE PATIENTS PRESENTING AT TERTIARY CARE HOSPITAL - KHAN , SU; SHAH , MA; SALAM , N; BALOCH , SK; SYED , FN; RIZVI , SAF (Biological and Clinical Sciences Research Journal, 2023)
A cross-sectional study was conducted at the Department of Pathology, Sharif Medical and Dental College Lahore, Pakistan, from January 2023 to June 2023. The total no of patients was 120 presented with chronic liver disease. The frequency of acquired dysfibrinogenemia was determined. The Chi-Square test with a P value < 0.05 as significant was used for the association between categorical variables. Most of the patients presenting were male patients compared to female patients. The frequency of acquired dysfibrinogenemia was 45 (38.3%). We found a significant association between acquired dysfibrinogenemia and the severity of the disease on the Child-Pugh Score. Our study concluded that the frequency of acquired dysfibrinogenemia in chronic liver disease patients was 45 (38.3%).